Russian doctors' health. Clinico-epidemiological analysis - S. A. Shalnova; R. G. Oganov; A. D. Deev; S. K. Kukushkin (Кардиоваскулярная терапия и профилактика)
Aim. To assess some aspects of Russian doctors' health.Material and methods. The analysis included data on 2347 doctors from various Russian cities: 326 men, 2021 women; mean age 43,6±0,23 years; mean time of working in present speciality 18,2±0,3 years. The participants included 480 cardiologists (20,4%), 1241 therapeutists (52,9%), and 626 doctors of other specialties (26,7%).Results. Awareness on cardiovascular disease (CVD) risk factors was relatively low: total cholesterol (TCH) level was unknown to 56,4% of men and 44,7% of women, glucose level was unknown to 38,4% and 28,8%, respectively. At the same time, high TCH level prevalence was 29,5% in men and 40,0% in women. High heart rate was reported by 15% of doctors; 16,6% of men and 20,5% of women had body mass index >30 kg/m2. Smoking prevalence was 36,7% in men and 10,6% in women. Russian male and female doctors suffered from arterial hypertension (AH) in 32,1% and 30,3%, respectively. Among male doctors with AH, only 61,7% took antihypertensives, with effective treatment in every fifth person; among hypertensive female doctors, these figures were 79,6% and 39,4%, respectively. Self-evaluated health was "very good" in 4,6% of men and 2,4% of women; "good" - in >40% and one-third, respectively; "fair" - in 50,1% and 61,6%; and "poor" - in 4% of males and 3,9% of females. Stress at workplace was experienced "almost all the time" in 32% of male doctors and 45,6% of female doctors, "sometimes" - by 60,8% and 51,3%, respectively. High stress level was reported by 27,3% of men and 42,3% of women.Conclusion. Dear Colleagues, please take care of your health and treat yourself properly, because doctors' health determines their patients' health in the long run.